CTA Project Completion Report: CLIMARK - Dido Bashuna, Sabdiyo; Were, Thomas Obiero; Shiri, Mejury (Technical Centre for Agricultural and Rural Cooperation, 2020)
Building upon past work within the region, CTA designed the project CLIMARK to increase incomes and adaptive capacity of pastoral communities in Northern Kenya and Southern Ethiopia. CLIMARK’s main objectives were revitalising livestock markets to boost trade and enterprises and facilitate commercial offtake of livestock, improving preparedness to drought disaster through blended weather info system and mitigating risk of livelihood failure through promotion of livestock (weather) insurance. In the second year of the project, a new component aimed at increasing efficiency in livestock trade through optimisation of data was introduced on a pilot basis. In this regard, CTA’s integrated approach to resilience building is a departure from past initiatives in that it is holistic in nature, it is market based and aims to build sustainability.